Efgartigimod combined with rituximab helps improve the symptoms and reduce the use of corticosteroids in patients with MuSK antibody-positive MG: a single case report - Zheng, Xiujun; Wang, Jing; Cai, Tongtong; Zhou, Houshi (Frontiers in Immunology, 2026)
IntroductionMyasthenia gravis (MG) is an autoimmune disorder primarily affecting the neuromuscular junction. Muscle-specific receptor tyrosine kinase antibody (MuSK-Ab)-mediated MG often presents with bulbar weakness and is prone to crisis. Currently, conventional treatments show limited efficacy in MuSK-Ab-mediated MG, while rituximab therapy demonstrates favorable outcomes.Case presentationWe report a case of a patient who initially achieved symptom control with efgartigimod during an acute exacerbation but experienced symptom recurrence after subsequent rituximab treatment. Owing to poor tolerance to pyridostigmine and corticosteroids, and considering the established efficacy of efgartigimod in MuSK-Ab-positive MG, we opted for continued efgartigimod infusions. This approach quickly improved symptoms, achieved minimal symptom expression (MSE), and allowed faster tapering of corticosteroids and pyridostigmine.ConclusionWhile multiple studies have demonstrated the efficacy and safety of efgartigimod, large-scale studies remain necessary to further evaluate the feasibility of combination therapy with rituximab in MuSK-Ab-positive MG.